1998
DOI: 10.1016/s1074-5521(98)90633-0
|View full text |Cite
|
Sign up to set email alerts
|

Active-site mutants of the VanC2 d-alanyl-d-serine ligase, characteristic of one vancomycin-resistant bacterial phenotype, revert towards wild-type d-alanyl-d-alanine ligases

Abstract: Single-residue changes in the active-site regions of D-, D-ligases can cause substantial changes in recognition and activation of hydroxy or amino acids that have consequences for glycopeptide antibiotic efficacy. The observations reported here should provide an approach for combatting antibiotic-resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…The specificity of D-Ala:D-Lac ligases has been investigated by mutagenesis (21,23,34), threedimensional structure determination (14,16), and molecular docking of the LmDdl2 D-Ala:D-Lac ligase (35,36). These studies provide evidence that the omega loop plays a central role in substrate selectivity at subsite 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of D-Ala:D-Lac ligases has been investigated by mutagenesis (21,23,34), threedimensional structure determination (14,16), and molecular docking of the LmDdl2 D-Ala:D-Lac ligase (35,36). These studies provide evidence that the omega loop plays a central role in substrate selectivity at subsite 2.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for D-Ala:D-Ser ligase specificity is not fully understood due, in part, to the absence of three-dimensional structures for this family of enzymes. Previous studies of the VanC2 D-Ala:D-Ser ligase suggested that residues Arg-322 and Phe-250 corresponding to, respectively, Arg-324 and Phe-252 in VanG could be responsible for the greater affinity of the second binding site for D-Ser (21). However, the role of these residues in controlling substrate specificity has not been elucidated.…”
mentioning
confidence: 99%
“…VanA and VanB synthesize D-alanyl-D-lactate and VanC synthesizes D-alanyl-D-serine. [4][5][6] Therefore, it is thought that the altered substrate specificities are inherent characteristics of VanA, VanB, and VanC, and that Ddl recognize solely D-alanine as substrate.…”
mentioning
confidence: 99%
“…Using the three-dimensional structure of DdlB of Escherichia coli (13) and VanA from Enterococcus faecium (32), site-directed mutagenesis studies have defined the residues responsible for substrate specificity (13,21,23,24,35).The existence of two D-Ala:D-Ala ligase genes has been previously reported in E. coli and Salmonella enterica serovar Typhimurium (41). In this work we provide evidence for the first time that vancomycin-resistant Enterococcus gallinarum possess at least three dipeptide ligase genes, two encoding D-Ala:D-Ala ligases and the third encoding a D-Ala:D-Ser ligase.…”
mentioning
confidence: 99%
“…Using the three-dimensional structure of DdlB of Escherichia coli (13) and VanA from Enterococcus faecium (32), site-directed mutagenesis studies have defined the residues responsible for substrate specificity (13,21,23,24,35).…”
mentioning
confidence: 99%